1992
DOI: 10.1164/ajrccm/145.6.1321
|View full text |Cite
|
Sign up to set email alerts
|

A Self-complete Measure of Health Status for Chronic Airflow Limitation: The St. George's Respiratory Questionnaire

Abstract: A need was identified for a fixed-format self-complete questionnaire for measuring health in chronic airflow limitation. A 76-item questionnaire was developed, the St. George's Respiratory Questionnaire (SGRQ). Three component scores were calculated: symptoms, activity, and impacts (on daily life), and a total score. Three studies were performed. (1) Repeatability was tested over 2 wk in 40 stable asthmatic patients and 20 patients with stable COPD. The coefficient of variation for the SGRQ total score was 19%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

34
1,985
11
55

Year Published

2003
2003
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 2,735 publications
(2,135 citation statements)
references
References 4 publications
34
1,985
11
55
Order By: Relevance
“…Higher scores indicate poorer health-related quality of life. The scores are calculated after filling in an Excel file developed by the creators of the questionnaire [24,25]. The SGRQ is a validated tool for patients with airflow limitations [24].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher scores indicate poorer health-related quality of life. The scores are calculated after filling in an Excel file developed by the creators of the questionnaire [24,25]. The SGRQ is a validated tool for patients with airflow limitations [24].…”
Section: Methodsmentioning
confidence: 99%
“…The scores are calculated after filling in an Excel file developed by the creators of the questionnaire [24,25]. The SGRQ is a validated tool for patients with airflow limitations [24]. Swigris and colleagues reviewed the literature and found that the SGRQ was useful for measuring HRQL in patients with IPF [25].…”
Section: Methodsmentioning
confidence: 99%
“…Two instruments were used to measure health-related quality of life, namely the St. George's Respiratory Questionnaire (SGRQ) [39], a disease-specific health status questionnaire, and the RAND-36 [40], a generic health status questionnaire. The SGRQ consists of 76 items that measure 3 components: 'symptoms' (problems caused by specific respiratory symptoms), 'activity' (restriction of activities by dyspnea) and 'impacts' (impact on everyday life caused by the disease) (reliability: test-retest correlation r 0.92) [39].…”
Section: Outcome Measuresmentioning
confidence: 99%
“…The SGRQ consists of 76 items that measure 3 components: 'symptoms' (problems caused by specific respiratory symptoms), 'activity' (restriction of activities by dyspnea) and 'impacts' (impact on everyday life caused by the disease) (reliability: test-retest correlation r 0.92) [39]. The RAND-36, which is a Dutch translation of the MOS 36-item Short-Form Health Survey [41], consists of nine subscales.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…Health status and mood state were assessed at baseline by means of the St. George's Respiratory Questionnaire 12 (SGRQ) and the Hospital Anxiety and Depression (HAD) Scale, 13 respectively. The SGRQ is a well-validated measure of impaired health in COPD and consists of 3 component scores (symptoms, activity, and impacts) and a summary score calculated from the 3 components.…”
Section: Measurementsmentioning
confidence: 99%